Weekly training load distribution and relationships between external and internal load indicators in professional soccer players - Radziminski, L. (Journal of Physical Education and Sport, 2021)
The distribution of the weekly training load is an important factor that determines the match performance in soccer players. The main purpose of this study was to present the weekly training load of professional soccer players during the competitive season and to investigate which external load variables may affect the rating of perceived exertion. The external and internal training loads applied to 31 professional soccer players (age: 26.7 ± 4.85 years; height: 181.2 ± 6.64 cm; mass: 76.4 ± 6.87 kg) during the competitive period of the 2018/2019 season were investigated. The largest training volume was performed on Matchday-5 (M-5) and Matchday-3 (M-3), while the longest average distance in high-speed running (HSR) and sprinting was covered on Matchday-4 (M-4). The data on RPE provided by the players suggested that M-4 was the most intensive day of the training week. The values for the most external and internal load indicators for Matchday-2 (M-2) and Matchday-1 (M-1) were significantly lower than during other days of the microcycle. Significant correlations were found between RPE and total distance (TD; r = 0.58, p < 0.001), HSR (r = 0.51, p < 0.001), sprinting (r = 0.25, p < 001), number of accelerations (r = 0.49, p < 0.001), number of decelerations (r = 0.56, p < 0.001), energy expenditure (r = 0.59, p < 0.001), average heart rate (HR avg) (r = 0.38, p < 0.001) and session duration (r = 0.37, p < 0.001). A progressive decrease in training loads from the middle of the week was observed in this study. Thus, variables, such as energy expenditure, TD, HSR distance and number of accelerations and decelerations determine the subjective fatigue of professional soccer players.